Nowe studia modernistyczne i późny modernizm - Kącka, Eliza (Poznańskie Studia Polonistyczne. Seria Literacka, 2014)
studies into late modernism—of the issues which are worth researching or the problems which should be signalled. The article starts with a recognition of a poor presence of the category of modernism in thinking about the literature of the 20th and 21st centuries and submits several proposals. At the beginning, a proposal of confronting a modernist paradigm with a paradigm of Romantic revision. This proposal was presented with an awareness of the fuzziness of the notion of modernism as well as the notion of Romantic revision in Polish academic environment. The following research postulates that would be formulated are: deeper reflection on the language (in connection with tradition, heritage and their problematization) and on the practices of reading. Later, the text poses a question about the way of studying the permeation of discourses in the writing of specific representatives of modernism and demands greater recognition for the Central European perspective in research.